Molecular detection and characterization of tick-borne hemoparasites and Anaplasmataceae in dogs in major cities of Malawi - Chatanga, Elisha; Kainga, Henson; Razemba, Tinotenda; Ssuna, Richard; Swennen, Lieza; Hayashida, Kyoko; Sugimoto, Chihiro; Katakura, Ken; Nonaka, Nariaki; Nakao, Ryo (Parasitology research (1987), 2021)
Tick-borne pathogens (TBPs) in dogs have attracted much attention over the last decade since some are now known to be zoonotic and pose a threat to both animal and human health sectors. Despite the increase in the number of studies on canine TBPs worldwide, only a few studies have been conducted in resource-limited countries where research priority is given to food animals than companion animals. In the present study, the occurrence of TBPs of the genera Babesia , Hepatozoon , Anaplasma , and Ehrlichia was investigated in 209 owned and stray dogs in three major cities in Malawi through molecular techniques. Among the examined dogs, 93 (44.5%) were infected with at least one TBP. The detection rates were 23.1% for Babesia rossi , 2.9% for B. vogeli , 19.1% for Hepatozoon canis , 2.4% for Anaplasma platys , and 3.8% for Ehrlichia canis. This is the first molecular study that has provided evidence that dogs in Malawi are infected with TBPs . Sensitization is required for veterinary practitioners, dog handlers, and pet owners as the detected pathogens affect the animals’ wellbeing. Further studies focusing on rural areas with limited or no access to veterinary care are required to ascertain the extent of the TBP infection in dogs.